Buletin Peternakan : Estimasi Sintesis Protein Mikrobia Rumen Menggunakan Ekskresi Derivat Purin dalam Urin dengan Teknik Spot Sampling pada Kambing Bligon dan Kambing Kejobong - Dianestu Putra, Lies Mira Yusiati, Ristianto Utomo (Peternakan UGM, 2016)
This study were aimed to determine the correlation between concentration of purine derivatives (PD) in spot sample with PD total excretion in Bligon and Kejobong goats and determine the appropriate sampling time, in order to predicting microbial protein synthesis in both breeds.